Application of Bottle SOSA And Promotions To Reduce The Risk Of Transmission Of Pulmonary TB In Men's Prison, Deli Serdang District - Sarumpaet, Sorimuda; Tarigan, Lina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. A report from the Ministry of Law and Human Rights of North Sumatra Province stated that during the period 2009-2011, new cases of pulmonary TB in prison / remand centers tended to increase every year, the increase was an average of 7.2%. Based on the above background, dedication needs to be done to apply the SOSA bottle along with the promotion of prevention of pulmonary TB transmission in an effort to reduce the incidence of pulmonary TB in assisted residents in the Male Prison, Deli Serdang Regency. Community service activities have been carried out with the socialization of the SOSA bottle application method which is carried out by the method of providing counseling videos and training for the introduction of SOSA bottles as a promotional medium in reducing the risk of pulmonary TB transmission. The WBP was recruited to attend training and become a Training of Trainer (TOT) by forming a peer group of 10 small groups in each prison. It is hoped that the service activities can continue with good cooperation with partners.